KOSTUM OLAHRAGA DALAM FOTOGRAFI FASHION - Maisy Audina (Specta: Journal of Photography, Arts, and Media, 2020)
Sport Costume in Fashion Photography. The creation of this commercial photography work features costume from self-defense, big balls, small balls and athletics. The process of shooting sport costume showed some of costume and action movement  of athlete without a human model, thus creating a fashion photography work that is packed in different forms and displays the action of movement in accordance with  costume of sports in fashion photography. The idea of visualizing different sport of costume with each other is very capable to evoke a remarkable imagination and have the uniqueness to be presented into the form of fashion photography. ABSTRAKPenciptaan karya fotografi komersial ini menonjolkan kostum dari cabang olahraga beladiri, bola besar, bola kecil dan atletik. Proses pemotretan kostum olahraga menampilkan kostum dan aksi gerak atlet tanpa model manusia, sehingga menciptakan karya fotografi fashion yang dikemas dalam bentuk berbeda dan menampilkan aksi gerakan sesuai dengan kostum olahraga dalam fotografi fashion.  Ide memvisualisasikan kostum olahraga yang berbeda satu sama lain sangat mampu untuk membangkitkan imajinasi yang luar biasa serta mempunyai keunikan untuk dipresentasikan ke dalam bentuk karya fotografi fashion.